2010
DOI: 10.1002/cssc.201000093
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Aqueous‐Phase Reforming and KOH Carbonation to Produce COx‐Free Hydrogen in a Single Reactor

Abstract: KOH is Key: A one‐pot multistep approach is developed for the production of COx‐free H2 from biomass‐derived oxygenates. By using KOH as process modifier, a gas product containing exclusively 97 % of H2 and 3 % of methane is obtained from aqueous‐phase reforming of ethylene glycol in a single reactor over an unmodified non‐precious‐metal catalyst. This approach enables the production of H2 in an energy‐efficient and cost‐effective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…To break this equilibrium, bases such as KOH and NaOH can be introduce into the APR reaction system and act as the stoichiometric agents to combine with the product CO 2 to form K 2 CO 3 and Na 2 CO 3 . This promoted the reaction to shift right and achieve a very high H 2 yield of greater than 90% (Liu et al, 2010). 4.1.4.2.…”
Section: Biofuelsmentioning
confidence: 99%
“…To break this equilibrium, bases such as KOH and NaOH can be introduce into the APR reaction system and act as the stoichiometric agents to combine with the product CO 2 to form K 2 CO 3 and Na 2 CO 3 . This promoted the reaction to shift right and achieve a very high H 2 yield of greater than 90% (Liu et al, 2010). 4.1.4.2.…”
Section: Biofuelsmentioning
confidence: 99%
“…Effect of modifiers on the APR of 5 wt-% ethylene glycol over Ni catalysts at 225 C, 25.8 bar, and WHSV ¼ 0.36 h ¡1[87].Fig. 12e Effect of hydrogen stripping with nitrogen on the ethylene glycol conversion and hydrogen selectivity of APR at 220 C and 35 bar[82].…”
mentioning
confidence: 99%
“…These results are in good agreement with the literature. In this sense, different authors 5,20,28,29 reported that the APR of glycerol was favored in terms of conversion and selectivity to H 2 with catalysts using basic supports or after addition of KOH to the substrate. Liu et al 29 suggested that basic medium provokes the polarization of H 2 O and in-duces its dissociation and/or directly provides the OH groups to be adsorbed onto the catalysts, which is an important step in the water-gas shift reaction.…”
Section: Aqueous Phase Reforming Runsmentioning
confidence: 99%
“…In this sense, different authors 5,20,28,29 reported that the APR of glycerol was favored in terms of conversion and selectivity to H 2 with catalysts using basic supports or after addition of KOH to the substrate. Liu et al 29 suggested that basic medium provokes the polarization of H 2 O and in-duces its dissociation and/or directly provides the OH groups to be adsorbed onto the catalysts, which is an important step in the water-gas shift reaction. 30 Likewise, He et al 31 and Liu et al 29 reported that addition of CaO or KOH to the initial biomass solution could in situ remove the CO 2 favoring the water-gas shift reaction by displacing the reaction towards the products and inhibiting methanation reactions.…”
Section: Aqueous Phase Reforming Runsmentioning
confidence: 99%